Expansible thermal gelling foam aerosol for vaginal drug delivery. (1st January 2017) - Mei, Liling; Chen, Jintian; Yu, Siqin; Huang, Ying; Xie, Yecheng; Wang, Hui; Pan, Xin; Wu, Chuanbin
Abstract: Vaginal delivery of antimicrobial drugs is the most effective method for the local treatment of the vaginal infections. However, current vaginal drug delivery systems (VDDS), including gel, lotion, aerosol and cream, are suffering from low penetration in the deep vaginal rugae and easy elimination by self-cleaning of vaginal canal. To address these issues, a foam aerosol based on the thermal transformation was designed to improve penetration efficiency and achieve the extended retention. The expansible thermal gelling foam aerosol (ETGFA) consisting of thermal sensitive matrix, silver nanoparticle, adhesive agent and propellant, was optimized by evaluations of precursor viscosity, foam expansion, thermal gelation, gel adhesiveness, antimicrobial effects and tissue irritation. The ETGFA would penetrate to the deep vaginal rugae to cover the infectious sites by foam expansion. Drug leakage was intended to be avoided by the thermal gelation at physiological temperature before foam collapse. The gel could be retained in the vaginal canal for extended time due to its superior adhesiveness when compared to the commercial gel Asimi ® . The ETGFA provided extended drug release for over 4 h and maintained effective drug concentrations at the infectious sites. The ETGFA containing silver nanoparticles showed dose-dependent antimicrobial effects on the vaginal floras and irritation reduction to the vaginal tissues. The results demonstrated that the ETGFA could overcome the limitations of conventional dosage forms, including poor drug penetration, carrier retention and patient compliance and satisfied the requirements for vaginal drug delivery.